PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR IPA SISWA SMP - Risjunardi Damanik (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the results of science learning outcomes of students in online learning using Google Meet and Google Classroom during Covid-19 pandemic. Population in this study were all class VIII as many as 210 students consisting of 7 classes. The sample in this study consisted of 2 classes with a total of 60 students. The sampling technique used was cluster random sampling technique and obtained 2 classes VIII-1 (Google Meet) and VIII-2 (Google Classroom). The type of this research is descriptive quantitative research using primary data analysis (questionnaire data) distributed using google form. The secondary data analysis was obtained from the School Final Examination data. The data were analyzed using SPSS 21 to get the mean, standard deviation (S), normality test, homogeneity test and hypothesis testing (t-test) at a significant level = 0.05. The results of hypothesis testing using SPSS obtained a significant 0.012 from t count (2.679), significant level = 0.05 and (df) = 58 obtained t table (2.001). If t count > t table is 2.679 > 2.001, then Ho is rejected and Ha is accepted, which means, there is an effect of online learning on junior high school students' learning outcomes. In terms of learning outcomes, classes that use Google Meet have higher learning outcomes than classes that use Google Classroom.